As filosofias da história e a tese da secularização: a teologia cristã e as raízes da secularização na modernidade / The philosophies of history and the secularization thesis: Christian theology and the roots of secularization in modernity - Aguiar de Souza, Jose Carlos (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2011)
<!–[if gte mso 9]> 1024x768 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> Ao negar a legitimidade da modernidade, Karl Löwith afirma que o surgimento das filosofias modernas da história são exemplos inequívocos de que os autores modernos simplesmente tomaram o padrão da escatologia cristã de forma secularizada. Ao contestar a tese de Löwith, Blumenberg afirma que a raiz da secularização na modernidade deve ser buscada na própria teologia cristã, sobretudo, com o conceito teológico de creatio ex nihilo: ao invés da secularização da escatologia o que houve foi uma secularização pela escatologia. <!–[if gte mso 9]> 1024x768 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Abstract Karl Löwith challenges the very foundations of the modern age with his thesis of secularization: the derivation of modern philosophies of history, with their celebration of progress, from Christianity. There are hidden theological presuppositions of modern historical consciousness, as exemplified by the thinkers of the 18th and 19th centuries. In other words, the secularization thesis reduces the modern age to a disguised version of Christian eschatology. Blumenberg’s outstanding work, The Legitimacy of the Modern Age, stands up to the underlying presuppositions of Löwith’s thesis. He introduces the concept of “secularization by eschatology” instead of “secularization of eschatology”.